British Virgin Islands : Financial Sector Assessment Program Update; Detailed Assessment of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2010)
The Banks and trust Companies Act, Financial Services Commission Act, and the Regulatory Act are considered for banking supervision. The assessment is also based on a self-assessment prepared by the Financial Services Commission (FSC). British Virgin Islands (BVI) law provides three classes of banking licenses. The preconditions for effective banking supervision are present in the BVI. The FSC has sufficient autonomy, powers, and resources with clear responsibilities and objectives. The FSC does not impose specific limits on investments but reviews bank-imposed limits. The FSC has a well-developed system of ongoing supervision in place.